Development Of Intercultural Communicative Competencies Of Students Based On Multimedia Tools - Tleumuratova Abadan Bekbanovna (Genius Journals, 2023)
The integration of Uzbekistan into the world educational space necessitates the search for new pedagogical technologies and solutions that ensure the activation of cognitive activity and motivation for obtaining knowledge of students. Uzbekistan needs highly qualified specialists who can simultaneously speak several levels – economic, social and cultural – of a highly qualified foreign language, that is, communicate in a foreign language, have linguistic-social knowledge. In the process of National Education and education of Uzbekistan, the experience of using multimedia tools is being formed. Because this is a requirement of the time at the same time. Developing information tools along with traditional opportunities that determine the basis of social development in our society are such factors as the ability of people, their creative approach to work, their intellectual activity, their independent improvement of their knowledge and skills. The process of creating information related to the storage, transmission, reception of a large amount of information provides for the development of human activities in various spheres of computer technology
Keywords: cultures; multimedia tools; international culture